An interactive 24-hour recall for assessing the adequacy of iron and zinc intakes in developing countries - Gibson, Rosalind S.; Ferguson, Elaine L. (International Food Policy Research Institute, 2008)
The manual has been written as a tool for program planners, experienced health professionals, and nutritionists wishing to measure intakes of iron and zinc and evaluate their adequacy in developing countries. It may also be useful for training nutritionists and nutritional epidemiologists in developing countries.